A New Multi-Purposes Flume Experiments Facility: Challenges and Opportunity for Tsunami and Coastal Engineering in Indonesia - Syamsidik, Syamsidik; Benazir, Benazir; Pratama, Nadri; Arifullah, Arifullah; Fatimah, Eldina; Nazaruddin, Nazaruddin; Tarmizi, Tarmizi; Ibrahim, Ibrahim; Zein, Ikramullah (TDMRC, Universitas Syiah Kuala, 2023)
Physical modelling for tsunami engineering is rather difficult to conduct due to lack of comprehensive and advanced facilities to do so. Large number of simulations of the tsunami impacts were performed numerically. In early 2023, a new advanced tsunami flume facility has been completed at Tsunami and Disaster Mitigation Research Center (TDMRC) of Universitas Syiah Kuala. This flume has 60 m in length, 2.5 m in width, and 1.7 m in height. The flume is also equipped with a number of wave, pressure, and current sensors, Particle Image Velocimetery (PIV) Camera, and a laser bed profiler. Beside of the tsunami generator, this flume is also capable to generate wind-driven waves (with two large wind turbines), regular and irregular waves, and currents. The flume provides new opportunities as well as challenges for tsunami scientists and engineers in Indonesia to collaborate and to perform novel researches in tsunami mitigation. This article is aimed at elucidating technical challenges and opportunities in performing tsunami physical models with the large tsunami flume. we performed a series numerical models using DualSPHysic. The results show that composite beach slopes inside the flume has succesfully mimic shallow coast effects that later deformed the incoming tsunami waves into breaking, bores, and runup. Challenges were identified in absorbing tsunami waves with more than one incoming wave to the observation area. In the future, this facility will be accessible for scientists and engineers to collaborate in tsunami science and engineering researches.